Development of Grating for the Optical Addressing of Sr+ Ions With Data Analysis Techniques - Yu Dian Lim; Peng Zhao; Luca Guidoni; Jean-Pierre Likforman; Chuan Seng Tan (IEEE Photonics Journal)
In this study, SiN-based gratings with various radius of curvature (r) are designed and fabricated for the optical addressing of trapped Sr+ ion. The beam width of the light coupled out from the gratings is investigated using a self-developed Python-based data analysis technique. It is found that the r values have insignificant influence on the beam width along x-axis; whereas the beam waist along y-axis reduces from 13.96 to 12.3 μm as r increases from 15 to 20 μm, then increases gradually to 20.51 μm as the r value further increases to 60 μm. The obtained results can provide a versatile solution on the optical addressing of trapped Sr+ for applications in quantum engineering.